Conservation of number: A comparison between cultures and subcultures - Roll, Samuel (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
To test the effects of cultural variation on conservation of number in children a United States sample was compared with a Colombian sample. Also 2 Colombian subgroups (middle class and working class) were compared. The U. S. data was gathered by previous investigators who worked with 58 conserving and non-conserving children.